Identification of Odorant-Binding and Chemosensory Protein Genes in Mythimna separata Adult Brains Using Transcriptome Analyses - Chen, Wen-Bo; Du, Li-Xiao; Gao, Xiao-Yan; Sun, Long-Long; Chen, Lin-Lin; Xie, Gui-Ying; An, Shi-Heng; Zhao, Xin-Cheng (Frontiers in Physiology, 2022)
Large numbers of chemosensory genes have been identified in the peripheral sensory organs of the pest Mythimna separata (Walker) to increase our understanding of chemoreception-related molecular mechanisms and to identify molecular targets for pest control. Chemosensory-related genes are expressed in various tissues, including non-sensory organs, and they play diverse roles. To better understand the functions of chemosensory-related genes in non-sensory organs, transcriptomic analyses of M. separata brains were performed. In total, 29 odorant-binding proteins (OBPs) and 16 chemosensory proteins (CSPs) putative genes were identified in the transcriptomic data set. The further examination of sex- and tissue-specific expression using RT-PCR suggested that eight OBPs (OBP5, -7, -11, -13, -16, -18, -21, and -24) and eight CSPs (CSP2–4, -8, CSP10–12, and -15) genes were expressed in the brain. Furthermore, bands representing most OBPs and CSPs could be detected in antennae, except for a few that underwent sex-biased expression in abdomens, legs, or wings. An RT-qPCR analysis of the expression profiles of six OBPs (OBP3–5, -9, -10, and -16) and two CSPs (CSP3 and CSP4) in different tissues and sexes indicated that OBP16 was highly expressed in male brain, and CSP3 and CSP4 were female-biased and highly expressed in brain. The expression levels of OBP5 and OBP10 in brain were not significantly different between the sexes. The findings expand our current understanding of the expression patterns of OBPs and CSPs in M. separata sensory and non-sensory tissues. These results provide valuable reference data for exploring novel functions of OBPs and CSPs in M. separata and may help in developing effective biological control strategies for managing this pest by exploring novel molecular targets.